Effect of copper concentration on structure morphology and optical band gap of spray deposited CZTS thin films - Mahewara, Ramesh B.; Ravangave, Limbraj S. (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2020)
Cu2ZnSnS4 (CZTS) films were deposited for five different molarity of Copper chloride (CuCl2) by using simple chemical spray pyrolysis technique at substrate temperature of (275±5)°C. Analytical Grade; Copper chloride (CuCl2), zinc chloride (ZnCl2), tin chloride (SnCl4.5H2O) and thiourea (SC (NH2)2) were used as sources of copper ( cu+), zinc (Zn+ ), tin ( Sn+) and sulfur ( S- ) ions respectively. A set of five CZTS films was deposited using five different molarity of CuCl2. The structure, morphology and optical properties of deposited CZTS films were studied using X-ray difractometer (XRD), Scanning Electron Micrographs (SEM) and UV-Visible spectroscopy respectively. The XRD spectra showed that all films are polycrystalline tetragonal crystal structure with Kesterite phase. The crystallite size estimated using full width at half maximum (FWHM) of (112) peak was increased with increase in concentration Cu+ ions. Optical band gap shows similar variation as that of crystallite size.